2014
DOI: 10.4103/0972-2327.132647
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse leptomeningeal gliomatosis: An autopsy case report

Abstract: Primary diffuse leptomeningeal gliomatosis (PDLG) is a rare condition, characterized by infiltration of the meninges by glial cells without evidence of the primary tumor in the brain or spinal cord parenchyma. Glioma arising primarily from the leptomeninges is extremely rare and often diagnosed only in post mortem examination and the diagnosis may be missed in meningeal biopsy. We describe a young female who presented with symptoms of raised intracranial pressure with imaging evidence of diffuse leptomeningeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Brain MRI in the begining of the disease usually shows normal findings. Later on hydrocephalus is developed, and diffuse thickening and contrast enhancement of the leptomeninges occurs [ 2 , 14 ]. CSF examination typically shows increased CSF pressure, hyperproteinorrhachia (up to 12.9 g/l in our patient) and lymphocytic pleocytosis with normal or lowered glucose amount can be present [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI in the begining of the disease usually shows normal findings. Later on hydrocephalus is developed, and diffuse thickening and contrast enhancement of the leptomeninges occurs [ 2 , 14 ]. CSF examination typically shows increased CSF pressure, hyperproteinorrhachia (up to 12.9 g/l in our patient) and lymphocytic pleocytosis with normal or lowered glucose amount can be present [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glial heterotopia is defined as nests or linear arrays of glial tissue in the meninges [2]. Primary leptomeningeal glioma can be in the form of a single solitary tumour or a diffuse tumour involving the intracranial or the spinal cord's leptomeninges [3]. The usual presentation includes symptoms and signs of raised intracranial pressure such as headache, nausea, vomiting, seizures, and papilloedema, and, based on a review of similar reported cases, it has been suggested that the presence of raised intracranial pressure with marked leptomeningeal enhancement on imaging should raise the suspicion of PDLG [3].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis relies mainly on the biopsy of meningeal tissue. For this reason, antemortem diagnosis is a challenge and approximately one-third of cases are diagnosed on postmortem examination [3]. Debono et al have proposed the following diagnostic criteria [4]:

No apparent attachment of extramedullary meningeal tumour to the neural parenchyma.

No evidence of primary neoplasia within the neuraxis.

The existence of distinct leptomeningeal encapsulation around the tumour.

A common finding on the imaging studies is the focal or diffuse leptomeningeal enhancement with contrast.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary type is caused by metastasis of glioma originated in the brain parenchyma; however, the primary type may arise from heterotopic glial cell nests in the pial surface of the brain and spinal cord, which can be found throughout the neuroaxis [ 12 ]. Prior to high resolution imaging, the definitive diagnosis of PDLG was dependent on autopsy to rule out a primary parenchymal source for the leptomeningeal seeding [ 6 , 7 , 13 ]. With the advent of improved imaging techniques, the diagnosis of PDLG is becoming more common and can be legitimately considered during the patient’s survive time, especially based on the gadolinium-enhanced MRI and biopsy [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to make a definitive diagnosis during the patient’s survival time [ 5 ]. Up to date, there are about 50 cases of PDLG having been reported in literatures, and more than half of patients are made a definitive diagnosis through postmortem [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%